2016
DOI: 10.3390/ijms17091446
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation of Bone Remodeling and Its Impacts in Osteoporosis

Abstract: Epigenetics describes mechanisms which control gene expression and cellular processes without changing the DNA sequence. The main mechanisms in epigenetics are DNA methylation in CpG-rich promoters, histone modifications and non-coding RNAs (ncRNAs). DNA methylation modifies the function of the DNA and correlates with gene silencing. Histone modifications including acetylation/deacetylation and phosphorylation act in diverse biological processes such as transcriptional activation/inactivation and DNA repair. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(62 citation statements)
references
References 110 publications
2
59
0
1
Order By: Relevance
“…It is reported that HDAC inhibition by TSA promotes osteoblast maturation in vitro , inhibits osteoclast differentiation of bone marrow cells4849 and mitigated osteoporotic injuries in animal studies50. Interestingly, previous studies reported that bone expressed low levels of Klotho5152 and we found that TSA also substantially recovered the Klotho loss in adenine mouse femurs, which likely exerting a local protective effects.…”
Section: Discussionsupporting
confidence: 57%
“…It is reported that HDAC inhibition by TSA promotes osteoblast maturation in vitro , inhibits osteoclast differentiation of bone marrow cells4849 and mitigated osteoporotic injuries in animal studies50. Interestingly, previous studies reported that bone expressed low levels of Klotho5152 and we found that TSA also substantially recovered the Klotho loss in adenine mouse femurs, which likely exerting a local protective effects.…”
Section: Discussionsupporting
confidence: 57%
“…Epigenetic mechanisms, in general, and DNA methylation, in particular, regulate gene expression in several diseases, including critical genes implicated in bone metabolism . A close interaction exists between immune and skeletal systems because of shared expression of several cytokines and transcription factors consistent with a role for osteoimmunology in bone disorders .…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that DNA methylation at various genes, including cyclin‐dependent kinases such as CDKN2A , plays a role in skeletal development, homeostasis, and bone cell activity. Thus methylation has been implicated in mechanisms of osteoblastic differentiation and osteoclastogenesis, together with the transition from osteoblast to osteocyte . These experimental findings are complemented by data from genome‐wide methylation profiling studies in older patients, demonstrating differential methylation at genes such as the cyclin‐dependent kinase inhibitor CKDN1C and cyclin‐dependent kinase CDK20 is associated with BMD .…”
Section: Introductionmentioning
confidence: 89%